2020
DOI: 10.1002/osi2.1093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of oral cancer in adolescent and young adult generation

Abstract: Purpose: To determine the clinical and therapeutic characteristics in adolescent and young adult (AYA) generation with oral cancer. Methods: We retrospectively studied AYA patients with oral cancer, aged 16-40 years who visited our department between 1 April 1997 and 31 December 2017, focusing on clinical characteristics including sex, age distribution, tumor site, pathological classification, stage, treatment, treatment outcome, and social rehabilitation. Results: Forty-two patients of AYA generation (19 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, the early detection of fatal diseases by referral from a family dentist to specialized hospital medical care is one of the indispensable functions for improving health maintenance. Yoshioka et al 13) reported that the diagnostic technique for oral cancer has improved and that oral function can be restored after treatment. Su cient oral hygiene was also reported to reduce the risk of esophageal cancer by Sepehr et al 14) .…”
Section: Prefacementioning
confidence: 99%
“…Therefore, the early detection of fatal diseases by referral from a family dentist to specialized hospital medical care is one of the indispensable functions for improving health maintenance. Yoshioka et al 13) reported that the diagnostic technique for oral cancer has improved and that oral function can be restored after treatment. Su cient oral hygiene was also reported to reduce the risk of esophageal cancer by Sepehr et al 14) .…”
Section: Prefacementioning
confidence: 99%
“…The role of the family dentist is not limited to supporting oral hygiene self-care. There have been reports on the detection of cancer in the oral cavity and the early detection of cancer [13,14]. Therefore, the early detection of fatal diseases by referral from a family dentist to specialized hospital medical care is one of the indispensable functions for improving health maintenance.…”
Section: Prefacementioning
confidence: 99%
“…Therefore, the early detection of fatal diseases by referral from a family dentist to specialized hospital medical care is one of the indispensable functions for improving health maintenance. Yoshioka Y, et al [13] reported that the diagnostic technique for oral cancer has improved and that oral function can be restored after treatment. Sufficient oral hygiene was also reported to reduce the risk of esophageal cancer by Sepehr A, et al [14].…”
Section: Prefacementioning
confidence: 99%
“…OLP has a female preponderance with chronic course, and erosive OLP shows a high potential for malignancy 2 3 . Therefore, the World Health Organization working group has categorized OLP as an oral potentially malignant disorder 4,5 .…”
Section: Introductionmentioning
confidence: 99%